2008
DOI: 10.1007/s10661-007-9906-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of visitors’ pressure on the spatial variability of sandy soil in an urban parks in Tel Aviv

Abstract: The effect of visitors' pressure on the spatial variability of soil properties was investigated in three open green areas in Tel Aviv. Six types of micro-environments were chosen: under oak and pine tree canopy with low (OL and PL) and high (OH and PH) visitors' pressure; herbaceous area without visitors' pressure (HE); and resting area under high visitors' pressure (RA). For each micro-environment soil samples were collected from the upper 0-5 cm depth for organic matter content and moisture determination. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Previously, Gomez-Limon and de Lucio (1995), Sarah and Zhevelev (2007), Zhevelev and Sarah (2008) and Hamberg et al (2010) reported fewer species and an impoverished structure of lower percentage cover and height in areas associated with visitor pressure. Floristic impoverishment pertains mainly to the group of forest plants including ancient forest species and geophytes, which are typical elements for natural forest communities in fertile habitats of oak–lime–hornbeam forests (Matuszkiewicz 2008).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previously, Gomez-Limon and de Lucio (1995), Sarah and Zhevelev (2007), Zhevelev and Sarah (2008) and Hamberg et al (2010) reported fewer species and an impoverished structure of lower percentage cover and height in areas associated with visitor pressure. Floristic impoverishment pertains mainly to the group of forest plants including ancient forest species and geophytes, which are typical elements for natural forest communities in fertile habitats of oak–lime–hornbeam forests (Matuszkiewicz 2008).…”
Section: Discussionmentioning
confidence: 95%
“…For particle size distributions between 0.01 and 2,000 μm, the laser diffraction method was applied. Selected soil properties in the upper soil layer (0–10 cm) were, according to Bhuju and Ohsawa (1998), Jim (1998), Haase et al (2000), Sarah and Zhevelev (2007) and Zhevelev and Sarah (2008), important factors affecting plant composition. The results of forest stand availability to off-trail visits are changes in the habitat and their effect on understorey vegetation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations